2020
DOI: 10.5755/j01.erem.76.2.23407
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Tin Compounds on the Lipid Peroxidation Level of Russian Sturgeon Fresh and Cryopreserved Sperm

Abstract: The effect of organotin compounds (OTs) on the accumulation of the lipid peroxidation (LPO) carbonyl by-products, which react with thiobarbituric acid (TBARS) in fresh and cryopreserved sperm of Russian sturgeon, was studied. It was found that incubation (1 hour) of Russian sturgeon sperm with OTs (CH3SnCl3, (CH3)2SnCl2, (CH3)3SnCl, (n-C4H9)2SnCl2, (n-C4H9)3SnCl, (C6H5)2SnCl2, (C6H5)3SnCl) in concentration 0.1 mM led to the promotion of the accumulation of TBARS in native semen. Dimethyl- (DMT) and dip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 29 publications
(32 reference statements)
0
4
0
Order By: Relevance
“…Currently, cryopreservation has a detrimental effect on the structural and functional parameters of Russian sturgeon spermatozoa [ 5 , 34 , 35 , 51 ]. Many factors influence the success of cryopreservation, including the initial quality of semen, the composition of the cryomedium, the cryoprotectant, the dilution factor, the concentration of spermatozoa used for cryopreservation, speed of freezing and thawing, as well as physiological aspects of sperm, such as species specificity [ 52 , 53 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Currently, cryopreservation has a detrimental effect on the structural and functional parameters of Russian sturgeon spermatozoa [ 5 , 34 , 35 , 51 ]. Many factors influence the success of cryopreservation, including the initial quality of semen, the composition of the cryomedium, the cryoprotectant, the dilution factor, the concentration of spermatozoa used for cryopreservation, speed of freezing and thawing, as well as physiological aspects of sperm, such as species specificity [ 52 , 53 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…The main causes and direct threats to sturgeon survival in the Danube River are overfishing, natural habitat destruction, pollution, and disruption of sturgeon migration routes. In addition to the legislative and financial measures taken in an attempt to fight off this ongoing natural disaster, sturgeon aquaculture has gained importance over the past years [ 4 , 5 ]. In nature, seasonal factors, such as water temperature and photoperiod play the main role in the annual growth response and maturation cycle of sturgeons.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the other current issues studied in sperm cryopreservation in sturgeon is the effect of organotin components (OTs) on fresh and frozen sperm. It has been reported that the accumulation of OTs in the gonad in Russian sturgeon is a stress factor affecting the cells in the cryopreservation process and also this buildup may cause in vitro oxidative stress in sturgeon sperm, reduce gamete quality, and affect fertilization success [57].…”
Section: Sturgeon Sperm Cryopreservationmentioning
confidence: 99%